Characterization of methacrylated polysaccharides in combination with amine-based monomers for application in mortar. (15th July 2017) - Mignon, Arn; Devisscher, Dries; Vermeulen, Jolien; Vagenende, Maxime; Martins, José; Dubruel, Peter; De Belie, Nele; Van Vlierberghe, Sandra
Highlights: Smart pH-responsive superabsorbent polymers (SAPs) for mortar applications. Methacrylation of different polysaccharides with amine-based monomers. Moisture uptake capacities reaching 120% at 95% relative humidity. pH-responsive swelling capacities up to 110 times its own weight. Limited hydrolysis in cement filtrate solutions making them very promising. Abstract: Smart pH-responsive superabsorbent polymers (SAPs) could be useful for self-healing of cracks in mortar. They will swell minimally during the alkaline conditions of mixing, leading to only small macro-pores but will swell stronger with a lower pH when water enters the cracks. As such, polysaccharides (alginate, chitosan and agarose) were methacrylated and cross-linked with amine-based monomers (dimethylaminoethyl methacrylate and dimethylaminopropyl methacrylamide) to induce a varying pH-sensitivity. These materials showed a strong cross-linking efficiency and induced moisture uptake capacities up to 122% at 95% relative humidity with a negligible hysteresis. Additionally, interesting pH-responsive swelling capacities were obtained, especially for SAPs based on chitosan and agarose with values up to 110 gwater/gSAP. Most of these materials showed limited hydrolysis in cement filtrate solutions, making them very promising for use in mortar.